Optical Properties of Low Concentration Ratio Façade Integrated Solar Collectors - (:unkn) unknown (Australian PV Institute (APVI), 2015)
The optical properties of façade integrated solar collectors are largely dependent on the location and the direction that they are deployed at. The amount of radiation on the absorber plate will change with the time of the day and the season. As such the optical performance of the collector is a strong function of sun elevation and azimuth angle. In this regard a geometrical model that is a function of the elevation angle of the sun may provide a good approximation of optical performance of the proposed flat reflector façade solar collector. Therefore this paper develops and presents an experimentally validated geometrical relationship incorporated with the sun-earth geometric relationships to predict the optical characteristics of a façade integrated solar concentrator with flat reflectors.